The use of Veno-arterial Extracorporeal Membrane Oxygenation (VA-ECMO) for Acute High Risk Pulmonary Embolism: A Systematic Review - Munagala, Rohit; Patel, Humail; Sathe, Pranav; Singh, Avneet; Narasimhan, Mangala (Current Cardiology Reviews, 2025)
IntroductionPulmonary embolism (PE) associated with hemodynamic compromise, termed high-risk or massive acute PE (MAPE), is associated with increased morbidity and mortality. Despite advancements in procedural techniques and an increase in the availability of advanced therapies, the outcomes associated with high-risk PE remain poor. Here, we review the literature surrounding the use of Veno-arterial Extracorporeal Membrane Oxygenation (VA-ECMO), primarily as a bridging therapy, in patients presenting with high-risk pulmonary embolism.MethodsWe conducted a systematic review and meta-analysis utilizing PubMed/MEDLINE from database inception until March 2024. The terms “high-risk PE”, “massive PE” and “MAPE” were paired with “VA-ECMO”, “bridge therapy” and “solo therapy” along with related terms to find and analyze relevant studies. The primary outcome assessed was in-hospital mortality.ResultsMost comparative studies involved assessing VA-ECMO's utility as solo therapy vs as a bridge to advanced therapy. Out of the data involving VA-ECMO as solo therapy, most showed definite survival benefit in subset of populations with VA-ECMO's role being varied by age and cardiac arrest presence. A portion of studies were notable for finding no difference in outcomes; however no major retrospective determined negative effect of VA-ECMO. In head-to-head studies as a bridge, studies from multiple centers highlighted VA-ECMO's role in stabilizing and improving survival in massive PE prior to systemic or catheter directed thrombolysis. Follow-up studies were limited, however one retrospective showed 30-day mortality of 31% and the 1-year mortality of 54% post PERT call. Follow-up echocardiograms performed on survivors between 30-365 days from Pulmonary Embolism Response Team (PERT) activation interestingly all had normal Right Ventricular (RV) size and function with mild to no tricuspid regurgitation.ConclusionMost major literature supports the use of VA-ECMO as either solo therapy or a bridge to advanced therapy in MAPE with additional shock or cardiac arrest. However, further studies are needed to develop society guidelines for regular initiation in cases of MAPE.
Keywords: bridge therapy